A novel La3+–Zn2+–Al3+–MoO42− layered double hydroxides photocatalyst for the decomposition of dibenzothiophene in diesel oil. (18th June 2018) - Gao, Li-Guo; Gao, Ying-Ying; Song, Xiao-Li; Ma, Xiang-rong
ABSTRACT: A new type of photocatalyst, La 3+ -Zn 2+ -Al 3+ -MoO4 2− layered double hydroxide (LDH) (La:Zn:Al = 1:7:2), was prepared by a complexing agent-assisted homogeneous precipitation technique. The LDHs were used as catalysts for the desulfurization of diesel oil under UV irradiation. As revealed by the results, the catalyst showed superior desulfurization efficiency and recycling performance. Under UV irradiation, the desulfurization efficiency was 84% in 60 min. In La 3+ –Zn 2+ –Al 3+ –MoO4 2− LDHs, the introduction of MoO4 2− increased the interlayer space for promoting the adsorption of dibenzothiophene, and MoO4 2− might act as the active sites for the oxidation of dibenzothiophene, resulting in the high desulfurization efficiency.